ショウワキチ ニ オケル スノウドリフト ケイゲン ノ タメニ ジッシ シタ ユキタイサク - 石沢, 賢二; イシザワ, ケンジ; Ishizawa, Kenji (2014)
P(論文) 昭和基地の建物周辺と除雪した道路のスノウドリフトを少なくし,ひいては第53 次日本南極地域観測隊による越冬中の除雪作業を軽減するため,次に挙げるいくつかのスノウコントロールを実施した.まず,汚水処理棟高架通路下部の雪と氷を排除し,吹き払い柵を設けて高架通路下部を風が高速で流れるようにした.基地中心部から離れた2 つの高床式建物では,建物と風下のスノウドリフトの間を除雪し,高床下部を風が通り抜けるように維持した.また,空ドラム缶を連結して導風ダクトを製作し,建物のドア前にスノウドリフトが発生しないようにした.さらに,幹線道路の除雪に際し,道路の風下側に排除した雪を置き,新たなスノウドリフトを少なくする工夫をした.以上のような日常的なメンテナンスを行うことにより,除雪の労力を減らすことができた.特に前次隊までたびたび行っていた汚水処理棟と倉庫棟屋根の雪下ろしは,A 級ブリザード後に数時間行うだけで済んだ.また,清浄大気観測小屋や大型大気レーダー小屋でも除雪の労力は大幅に減った.さらに,基地燃料ポンプ小屋とプロパンボンベ庫ドア前のスノウドリフト付着は最小限に食い止められた.見晴らし道路除雪後のスノウドリフトもほとんどなく,再度除雪することはなかった. Snow controls were employed to reduce snow drifts around buildings and a main road during the period of the 53rd Japanese Antarctic Research Expedition (JARE-53) wintering party at Syowa Station. Snow and ice that accumulated under the elevated areaway of a sewage treatment building were removed and a blower fence was erected. Wind passages under highfloored buildings were maintained by cutting openings through snow drifts that developed on the leeward side of the buildings. Empty drums were useful as wind ducts to prevent snow drifts from accumulating in front of doors of small huts. Snow removed from along a main road was relocated on the leeward side of the road to prevent the subsequent accumulation of snow drifts. departmental bulletin paper